(untitled) (Серія: Історія. Політологія, 2021)
It is proved that Brexit has political and socio-economic implications for UK development. It is grounded that one of the consequences of Brexit may be a further fragmentation within the UK itself. London experiences many contradictions in relations with Scotland, Wales and Northern Ireland nowadays. In Scotland, after the referendum on the independence of the autonomous region, in which 55% of Scots opposed the secession from the UK in 2014, the movement for independence has strengthened its position. Part of the rise in such sentiment in Scottish society is due to concerns over Brexit. In 2021 the unity of the UK’s autonomous regions may be threatened by the strengthening of nationalist sentiments in Scotland, as well as in Northern Ireland and Wales. The Scots do not want to lose the economic benefits of a duty-free customs regime with the EU and historic ties with Europe. Leaving the EU common market will be a devastating blow to investment and employment in Scotland. A break with London will also be costly, as Scotland’s economy has close ties with the UK.